(untitled) (Bangladesh Journal of Botany, 2010)
Four taxa of Oedogonium Link in Nees growing on different hydrophytes in Rajshahi district such as, O. acrosporum var. acrosporum De Bary, O. areschougii Wittr. Hirn var. contortifilum Jao, O. khannae Skuja f. minus Gonz. et Jain and O. striatum Tiff. var. denticulatum Gauthier-Liev. have been recorded for the first time from Bangladesh. Key words: New records; Oedogonium; Green algae; Bangladesh DOI: 10.3329/bjb.v38i1.5115 Bangladesh J. Bot. 38(1): 27-31, 2009 (June)